2017
DOI: 10.1016/j.canlet.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in gynecological cancers: Small molecules with big implications

Abstract: Gynecological cancers (GCs) are often diagnosed at advanced stages, limiting the efficacy of available therapeutic options. Thus, there remains an urgent and unmet need for innovative research for the efficient clinical management of GC patients. Research over past several years has revealed the enormous promise of miRNAs. These small non-coding RNAs can aid in the diagnosis, prognosis and therapy of all major GCs, viz., ovarian cancers, cervical cancers and endometrial cancers. Mechanistic details of the miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 314 publications
0
73
0
Order By: Relevance
“…Among the miRNAs differentially expressed in EC versus normal endometrial tissue are the increased expression of miR-10b, miR-21, miR-31, miR-182, miR-183, miR-205, miR-222, miR-223, miR-410, miR-429, miR-449a, miR-994, and miR-1228; and downregulation of let-7, miR-34b-5p, miR-34c-3p, miR-34c-5p, miR-99b, miR-101, miR-130a, miR-143, miR-145, miR-184, miR193b, miR-204, miR-340, miR-372, miR-429, miR-449a, miR-490, and miR-495 (reviewed in (Srivastava, et al 2017)). In serum samples from women with EC, increased levels of miR-186, miR-222, and miR-223 were identified compared with controls (Montagnana, et al 2017).…”
Section: Dysregulation Of Mirnas In Ecmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the miRNAs differentially expressed in EC versus normal endometrial tissue are the increased expression of miR-10b, miR-21, miR-31, miR-182, miR-183, miR-205, miR-222, miR-223, miR-410, miR-429, miR-449a, miR-994, and miR-1228; and downregulation of let-7, miR-34b-5p, miR-34c-3p, miR-34c-5p, miR-99b, miR-101, miR-130a, miR-143, miR-145, miR-184, miR193b, miR-204, miR-340, miR-372, miR-429, miR-449a, miR-490, and miR-495 (reviewed in (Srivastava, et al 2017)). In serum samples from women with EC, increased levels of miR-186, miR-222, and miR-223 were identified compared with controls (Montagnana, et al 2017).…”
Section: Dysregulation Of Mirnas In Ecmentioning
confidence: 99%
“…Targets of upregulated miRs in EC include the tumor suppressor PTEN that is downregulated by overexpressed miR-21, miR-130a, miR-205, miR-222, and miR-429 (Srivastava et al 2017). …”
Section: Dysregulation Of Mirnas In Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated miRNAs can regulate the malignant behaviours of cancer cells, including proliferation, cell cycle, migration and invasion, through targeting and regulating various oncogenes or tumour suppressors . To date, a growing body of evidence has demonstrated that various miRNAs participate in the development and progression of cervical cancer and can be utilized as biomarkers for the diagnosis and prognosis of the disease, as well as therapeutic targets . Therefore, better understanding of the miRNA‐regulated molecular mechanisms occurring throughout cervical cancer progression will help researchers to develop novel miRNA‐based anticancer therapy for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many studies have analyzed the expression patterns of miR-NAs in different tumor entities and correlated them with the prognosis of the individual patient. [4][5][6][7] Functionally miRNAs can modulate the proliferation of tumor cells, 8 the migration and the metastatic potential, 9 the process of epithelialmesenchymal transition 8,9 or the sensitivity of tumor cells to chemotherapy. 10 MiRNAs also regulate the adequate development of tissues and organs.…”
Section: Introductionmentioning
confidence: 99%